2011
DOI: 10.1080/17437199.2011.570516
|View full text |Cite
|
Sign up to set email alerts
|

Social psychological factors of post-mortem organ donation: a theoretical review of determinants and promotion strategies

Abstract: A recurrent observation in the field of organ donation is that organ demand exceeds supply. Organ donation promotion is therefore required in order to diminish this gap. In this article, we focus on post-mortem organ donation and review psychosocial literature contributing to identify firstly, the determinants of donation, and secondly, the factors likely to increase the efficiency of donation promotion campaigns. Finally, we discuss the theoretical implications of our review and advance promising avenues for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 18 publications
1
61
1
7
Order By: Relevance
“…It has previously been claimed that the modality of communication in itself makes little difference to the effectiveness of organ donation campaigns, although interactions may occur between modality of messages and individuals’ characteristics (Falomir‐Pichastor, Berent, & Pereira, ). It was striking in Study 2 that in face‐to‐face mode, intentions in the control and reciprocity prime conditions were identical.…”
Section: Overall Discussionmentioning
confidence: 99%
“…It has previously been claimed that the modality of communication in itself makes little difference to the effectiveness of organ donation campaigns, although interactions may occur between modality of messages and individuals’ characteristics (Falomir‐Pichastor, Berent, & Pereira, ). It was striking in Study 2 that in face‐to‐face mode, intentions in the control and reciprocity prime conditions were identical.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Bu durum ölümün kesinliğiyle, fedakarlıkla, organ ihtiyacı olan diğer çocuklara karşı duyulan empati ile açıklanmaktadır (14,15). Ebeveynler için muhtemelen hayatlarının en zor anı, çocuklarının beyin ölümü hakkında bilgilendirme yapıldıktan sonra, organ bağışı hakkındaki kararlarının sorulduğu andır.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…Amerika, Avusturya ve İngiltere gibi büyük ülkelerin de dahil olduğu 50'den fazla ülkenin organ transplantasyonu ihtiyacının karşılanmasındaki en büyük engellerden biri aile rızasının gerekli olması ve rıza oranlarının düşük olmasıdır (13). Yapılan araştırmalar ailelerin organ bağışına rıza göstermesini etkileyen birçok farklı psikososyal faktörün olduğunu göstermiştir (14,15).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Breadths of studies have suggested that the impact of SC on behavior intention may predict global health behaviors, given the strong links between comparison motivation and behavioral action (Arigo et al, 2012;Falomir-Pichastor, Berent, & Pereira, 2013). Bailis and Segall (2004) assessed prospective wellness-center membership with the goal of addressing the interaction between motivational factors and SC cognitions.…”
Section: Interaction Between Motivation and Direction Of Social Compamentioning
confidence: 99%